Reality Show: The Influence of Destination Exposure to Viewers’ Travel Intention - Mege, S R (Universitas Negeri Manado, 2019)
Reality show has started to dominate the television industry and has been used as media for product placement strategy. Destination placement in reality show serves the same purpose. However, previous study in destination placement in reality show is limited, as well as the study about travel intention to destination through reality show. The purpose of this study is to examine the influence of destination exposure in reality show to viewers’ travel intention to the destination. This study was conducted using experimental method, involving one hundred and four undergraduate students distributed randomly into experiment and control group. The stimulus used in this study was the popular reality show, The Amazing Race. The data was analyzed using independent sample t-test. The result of this study showed that in general viewers who received exposure of destination in reality show had higher travel intention to the destination, and in specific triggered the awareness and interest to look for information about the destination.